Targeting Mitochondrial Oxidative Phosphorylation Eradicates Acute Myeloid Leukemic Stem Cells - Peng, Meixi; Huang, Yongxiu; Zhang, Ling; Zhao, Xueya; Hou, Yu (Frontiers in Oncology, 2022)
Acute myeloid leukemia (AML) is a heterogeneous hematologic malignancy characterized by multiple cytogenetic and molecular abnormalities, with a very poor prognosis. Current treatments for AML often fail to eliminate leukemic stem cells (LSCs), which perpetuate the disease. LSCs exhibit a unique metabolic profile, especially depending on oxidative phosphorylation (OXPHOS) for energy production. While, normal hematopoietic stem cells (HSCs) and leukemic blasts rely on glycolysis for ATP production. Thus, understanding the regulation of OXPHOS in LSCs may offer effective targets for developing clinical therapies in AML. This review summarizes these studies with a focus on the regulation of electron transport chain (ETC) and tricarboxylic acid (TCA) cycle in OXPHOS, and discusses potential therapies for eliminating LSCs.